Trends in death certification for multiple sclerosis, motor neuron disease, Parkinson's disease and epilepsy in English populations 1979-2006. - Goldacre, M; Duncan, M; Griffith, M; Turner, M (2010)
The objective of this study is to report trends in mortality, as certified on death certificates, from multiple sclerosis (MS), motor neuron disease (MND), primary Parkinson's disease (PD), and epilepsy, analysing not only the underlying cause of death but also all certified causes for each disease. Death records in the Oxford region, 1979-2006, and England, 1996-2006, were analysed for ascertaining the trends in mortality. The percentage of deaths coded as the underlying cause changed over time, coinciding with changes to the rules for selecting the underlying cause of death. Changes over time to coding rules had a large impact on apparent trends in death rates for PD when studied by underlying cause alone. They also had significant, though smaller, effects on trends in death rates for MS, MND and epilepsy. Nationally, in the last period of the study, underlying cause mortality identified 64% of deaths with a mention of MS, 88% of MND, 56% of PD, and 48% of epilepsy. In the longstanding Oxford data from 1979 to 2006, death rates based on all certified causes of death showed no significant change for MS; an upward trend for MND (notably in women over 75), though only in the last few years of the study; a significant but small decline for PD; and no significant change for epilepsy. When mortality statistics are analysed by underlying cause only, their value is reduced. A substantial percentage of neurological deaths are missed. Time trends may be misleading. All certified causes for each disease, as well as the underlying cause, should be analysed.